Effect of adding 2-ethylhexyl nitrate cetane improver on the autoignition properties of ethanol–diesel fuel blend – Investigation at various ambient gas temperatures. (15th July 2018) - Kuszewski, Hubert
Highlights: Ignition delay period for ethanol–diesel fuel blend with 2-EHN was measured. Tests of autoignition properties were conducted for different ambient gas temperatures. During investigation, the constant volume combustion chamber was used. Derived cetane numbers for fuel samples were determined. Abstract: One of the alternative fuels considered for powering piston internal combustion engines is ethanol. In some countries, ethanol has been successfully used for many years as a self-contained fuel in positive-ignition engines after relatively minor technical modifications. Due, among other things, to a very low cetane number, this fuel cannot be used in pure form in diesel engines. Consideration is being given to fuels that are blends of diesel fuel with some ethanol fraction. Diesel fuel containing up to 15% (v/v) of ethanol is sometimes referred to as e-diesel or oxygenated diesel. However, it is necessary to improve the autoignition properties of such a blend. Improvement of the autoignition properties of an ethanol–diesel fuel blend (EDB) can be accomplished by introducing an additive that improves the propensity for autoignition. One such additive may be 2-ethylhexyl nitrate (2-EHN), which is commonly used to improve the autoignition properties of diesel fuels. This study determined the effect of the addition of 2-EHN (up to 10, 000 ppm [m/m]) on the autoignition properties of an EDB with an ethanol fraction of 15% (v/v). The study was carried out by using a device with a constant volume combustion chamber, which additionally enabled determination of the effect of the ambient gas temperature (in the range 550–650 °C) on the period of ignition delay and the period of combustion delay, as well as the derived cetane number. The average and maximum pressure rise rates in the combustion chamber were also analysed. Studies have shown that, with an increase of the 2-EHN fraction in an EDB, the periods of ignition and combustion delay decrease, and the increase in the temperature of ambient gas into which the fuel is injected shortens these periods to a varying extent.